Does good luck make people overconfident? Evidence from a natural experiment in the stock market - Gao, Huasheng; Shi, Donghui; Zhao, Bin (Journal of Corporate Finance, 2021)
This paper examines the changes in investors' trading behavior after winning an IPO allotment in China—a purely luck-driven event. We find that these investors subsequently become overconfident: They trade more frequently and lose more money relative to other investors. This effect is stronger when investors are inexperienced and when investors' pre-existing level of overconfidence is low. We also show that investors exhibit a stronger gambling propensity and hold more lottery-like stock after winning an IPO allotment. Our findings are not explained by wealth effects or house money effects. Overall, our evidence indicates that the experience of good luck makes people overconfident about their prospects.